Over-optimistic patient expectations of recovery and leisure activities after arthroscopic meniscus surgery: A prospective cohort study of 478 patients. (1st November 2016) - Pihl, Kenneth; Roos, Ewa M; Nissen, Nis; JøRgensen, Uffe; Schjerning, Jeppe; Thorlund, Jonas B
Abstract : Background and purpose — Patients' expectations of outcomes following arthroscopic meniscus surgery are largely unknown. We investigated patients' expectations concerning recovery and participation in leisure-time activities after arthroscopic meniscus surgery and the postoperative fulfillment of these. Patients and methods — The study sample consisted of 491 consecutively recruited patients (mean age 50 (SD 13) years, 55% men) who were assigned for arthroscopy on suspicion of meniscus injury and later verified by arthroscopy. Before surgery, patients completed questionnaires regarding their expectations of recovery time and postoperative participation in leisure activities. 3 months after surgery, the patients completed questionnaires on their actual level of leisure activity and their degree of satisfaction with their current knee function. We analyzed differences between the expected outcome and the actual outcome, and between fulfilled/exceeded expectations and satisfaction with knee function. Results — 478 patients (97%) completed the follow-up. 91% had expected to be fully recovered within 3 months. We found differences between patients' preoperative expectations of participation in leisure activities postoperatively and their actual participation in these, with 59% having unfulfilled expectations (p < 0.001). Satisfaction with current knee function was associated with expectations of leisure activities being fulfilled/exceeded. Interpretation — In general, patients undergoing arthroscopic meniscus surgery were too optimistic regarding their recovery time and postoperative participation in leisure activities. This highlights the need for shared decision making which should include giving the patient information on realistic expectations of recovery time and regarding participation in leisure-time activities after meniscal surgery.